If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(2/9)x=(2/3)
We simplify the equation to the form, which is simple to understand
(2/9)x=(2/3)
Simplifying:
( + 0.222222222222)*x=(2/3)
Simplifying:
( + 0.222222222222)*x=( + 0.666666666667)
Reorder the terms in parentheses
( + 0.222222222222x)=( + 0.666666666667)
Remove unnecessary parentheses
+ 0.222222222222x=( + 0.666666666667)
Remove unnecessary parentheses
+ 0.222222222222x=0.666666666667
We move all terms containing x to the left and all other terms to the right.
+ 0.222222222222x=0.666666666667
We simplify left and right side of the equation.
+ 0.222222222222x=0.666666666667
We divide both sides of the equation by 0.222222222222 to get x.
x=3
| (4/7)(x-3)=(5/3) | | 6x+30-6=10 | | 10x-2=4x | | 6-7x=6x-10x-15 | | -2.09a=24 | | 2x-45=4x+15 | | (3/5)x-4=7x | | 40x^2-30x-25= | | 0.57t=8 | | 4(3-x)-(2-5x)-3(2x+8)=-5(3x-3) | | -2(j-3)=-2+6 | | (6/7)x=18 | | 8z-z=-1+4z-1-4 | | 5x+2n-3=-3x+10x | | 15x^2+50x+40= | | 3(x-4)-2(x+2)=5 | | 72=8x | | x+6(x-q)=7(3+x) | | -(r-6-4p)= | | 32=-6b-4 | | 2lu+2l-38=-10 | | 3(x-2)+4=8 | | 0.7=-0.2x | | 18x^2+66x+45= | | -3x=8(x+x)+3 | | x+1=31 | | -(2+4x)+5(3-x)=-5(3x-3) | | -20x-5= | | a+5b= | | x/3+2=-10 | | 3y+15=5y-20 | | 5-3(0,5x-1)=0,5x-14 |